Gender Perspectives of ICT Utilization in Agriculture and Climate Response in West Africa: A Review - Zougmoré, Robert B.; Partey, Samuel T. (MDPI, 2022)
This paper systematically reviewed the relevant literature to generate evidence and identify knowledge gaps on the gender perspectives of ICT use for agriculture and climate response in West Africa. It was evident from the literature that ICTs continue to form an important part of agricultural operations, climate response and agribusiness in West Africa. TV, radio and mobile phones were the most frequently used ICT platforms for receiving agricultural and climate information. Mobile phones have an added use for sales and financial transactions. There were no distinct gender differences in the use of ICTs for agriculture and climate response. However, women’s low income and limitations in controlling household financial responses were identified as significant barriers to ICT access. It was evident that ICTs may contribute to achieving gender outcomes in agriculture and climate response if an enabling environment is created for women to have access to the inputs and resources needed to implement agro-advisories. From the results obtained, there are clear indications that the gender perspectives of ICT use in agriculture and climate response has not received much research attention. The analyses identified important knowledge gaps on gender disaggregated information on the linkages among ICT use, agricultural productivity and climate adaptation indicators